Creativity in the cottage craft industry: the case of the Ugandan Nubian community - Amafua, Mahfuth Khamis; Mohammed, Mustafa Omar (2014)
The history of the Nubian community in Uganda is traced from the Ottoman rule over Egypt and Sudan in 1820. This predominant Muslim community was brought to Uganda and later became part of the British Army. Due to colonial Christianization of the education system in Uganda, the Nubians were forced out of public life. They had to sustain their livelihood through the cottage craft industry. Hitherto, there has hardly been any study that has documented their creativity and taken stock of the sustainability of this vibrant industry. The present study adopts qualitative approach to examine the extent of the sustainability of this cottage industry. Based on the results, the respondents are unanimous that the Nubians have managed to sustain their creativity, though in an informal structure; there is an urgent need to document their creativity and activities and the formation of strong community organizations in addition to capacity building can be instrumental in sustaining the craft industry through aggressive marketing. The paper proposes the use of quantitative survey and more robust methodology in future to enhance the quality and generalize findings of this important subject.